Adaptasi Pekerja Kuli Pantai Pada Masa Pandemik di Kelurahan Dabo Lama Kecamatan Singkep, Kabupaten Lingga - Wardi; Nanik Rahmawati; Rahma Syafitri (CV Insan Kreasi Media, 2023)
Singkep is the name of an island in the Riau Archipelago. In the course of its history, Singkep Island is a sub-district with the capital city in Dabo. Like other big cities in Indonesia. Lingga Regency is also not spared from population growth. Previously, Lingga Regency was a tin producer with a mining reputation for almost 2 (two) centuries (1812-1992), to be precise on Singkep Island. After PT tin or UPTS (Singkep Tin Mining Unit) closes, it leaves remnants of tin excavations such as holes that spread across Singkep Island and are not closed again causing the former excavation holes to collect water so that a pit is formed. Over time, settlements that were formerly residential areas of miners became urban areas and the number of divisions carried out by the government consisted of several sub-districts, sub-districts and several villages. The purpose of this study was to identify the adaptation of beach coolies during the Covid-19 pandemic in the Dabo Lama Village, Singkep District, Lingga Regency. This research was carried out using descriptive, qualitative methods with as many as 6 informants used in this study and using observation, interview and documentation data collection techniques and tools. The results of the study found that in this study, the people of the Dabo Lama sub-district during the pandemic experienced a change in society, which had always worked as stone and sand miners, laborers, gardeners, civil servants and the private sector. Now some have switched to new jobs, because people are trying to adapt to the surrounding environment, so that their living conditions can continue as usual. The impact that occurs is the loss of livelihood for workers, especially sand and stone mining workers and the occurrence of cultural shock with a new culture, but they are able to adapt